Mikheil Kavtaria as a Researcher of the History of the Georgian Church - Vardosanidze, Sergo (Actual Problems of Kartvelology, 2019)
Professor Mikheil Kavtaria was a great philologist, historian and textual scholar who researched with equal enthusiasm the history of Georgian literature, manuscripts and historic documents as well as the matters of the History of the Georgian Orthodox Apostolic Church. In ‘20s to‘80s of the 20th century, during the occupant and atheist government ruling, discussions around historic matters of the Georgian Orthodox Church could be manifested within the developmental frames of materialistic thinking of the Georgian culture. Among the secular scientists there was hardly anyone who would recount the centuries-old history of the Georgian Orthodox Apostolic Church impartially and with scientific honesty. Professor Mikheil Kavtaria was the only scientist who disregarded the official political conjuncture and objectively researched the history of the Georgian Church. Professor Mikheil Kantaria was well aware of historic facts and events of the 20th century Georgian Church that were hidden from the general public (the issue of co-regent During the Patriarch Ambrosi, December 1926 Congress in Kutaisi, inner intrigues and oppositions within the Church in 1950s and 1960s, Church revolt of 1968, the case of Metropolitan Gaioz Keratishvili). The person aware of the top priority information was remarkably reserved. This man, who seemed to be an open, free and friendly person, had high civic and scientific principles that no one could ever make him divert from. Mikheil Kavtaria would never praise vice or denounce virtue. He quietly pursued great deeds, preserved and kept alive the great history of the Georgian Church and to all of us served as an embodiment of a true scholar and a real patriot devoted to his cause and country. His passing brings us great pain however his scientific legacy and his name alike towering iceberg will shine in the Georgian intellectual sphere for many years to come.